Interregional Structure Analysis Based On Three Regions Of Vietnam - Trinh, Bùi (Advances in Social Sciences Research Journal, 2017)
The Leontief’s input-output system was developed to the inter-regional input-output model by Isard in 1951. The idea of the inter-regional input-output model was specified and extended by Miyazawa, Richardson, Yamada H, T. Ihara… and it is considered as an important tool in researching of regional economy. This article try to attempt description and analyzing three regions (Mekong Delta region, South East region and rest of Vietnam – ROV) based on multi interegional input-output table of Vietnam, 2005